Whole-Genome and Plasmid Comparative Analysis of Campylobacter jejuni from Human Patients in Toyama, Japan, from 2015 to 2019 - Daichi Morita; Hiroki Arai; Junko Isobe; Emi Maenishi; Takanori Kumagai; Fumito Maruyama; Teruo Kuroda (Microbiology Spectrum, 2023)
ABSTRACT Campylobacter jejuni is a major causative agent of food poisoning, and increasing antimicrobial resistance is a concern. This study investigated 116 clinical isolates of C. jejuni from Toyama, Japan, which were isolated from 2015 to 2019. Antimicrobial susceptibility testing and whole-genome sequencing were used for phenotypic and genotypic characterization to compare antimicrobial resistance (AMR) profiles and phylogenic linkage. The multilocus sequence typing approach identified 37 sequence types (STs) and 15 clonal complexes (CCs), including 7 novel STs, and the high frequency CCs were CC21 (27.7%), CC48 (10.9%), and CC354 (9.9%). The AMR profiles and related resistant factors were as follows: fluoroquinolones (51.7%), mutation in quinolone resistance-determining region (QRDRs) (GyrA T86I); tetracyclines (27.6%), acquisition of tet(O); ampicillin (7.8%), harboring blaOXA184 or a promoter mutation in blaOXA193; aminoglycosides (1.7%), acquisition of ant(6)-Ia and aph(3′)-III; chloramphenicol (0.9%), acquisition of cat. The acquired resistance genes tet(O), ant(6)-Ia, aph(3′)-III, and cat were located on pTet family plasmids. Furthermore, three pTet family plasmids formed larger plasmids that incorporated additional genes such as the type IV secretion system. Sequence type 4526 (ST4526; 10.9%), which is reported only in Japan, was the most predominant, suggesting continued prevalence. This study reveals the sequences of the pTet family plasmids harbored by C. jejuni in Japan, which had been unclear, and the acquisition of the insertion sequences in a part of the pTet family plasmids. Because pTet family plasmids can be horizontally transmitted and are a major factor in acquired resistance in Campylobacter, the risk of spreading pTet that has acquired further resistance should be considered. IMPORTANCE Campylobacter jejuni is among the major causes of enteritis and diarrhea in humans in many countries. Drug-resistant Campylobacter is increasing in both developing and developed countries, and in particular, fluoroquinolone-resistant Campylobacter was one of the species included on the priority list of antibiotic-resistant bacteria. Campylobacter drug resistance surveillance is important and has been conducted worldwide. In this study, we performed whole-genome analysis of Campylobacter jejuni isolated from diarrhea patients at a hospital in Toyama, Japan. This revealed the continued prevalence of Campylobacter jejuni ST4526, which has been reported to be prevalent in Japan, and the acquisition of resistance and virulence factors in the pTet family plasmids. The diversity of pTet family plasmids, the major resistance transmission factor, is expected to potentially increase the risk of Campylobacter. The usefulness of whole-genome sequencing in Campylobacter surveillance was also demonstrated.